In Search of the Chill: Access to Information and Record-keeping in the Government of Canada - Badgley, Kerry; Dixon, Margaret J.; Dozois, Paulette (Archivaria, 2003)
Debate over the Access to Information Act (ATIA) has centred on the government’s seeming unwillingness to comply with the law and its intention. While the Information Commissioner’s reports have highlighted breaches such as delays in responding to requests, or the overly broad application of the Act’s exemptions, others have argued that such legislation has only reinforced the government’s reluctance to be scrutinized via its records. Further, media reports on the investigations into the possible destruction of records, such as the war diaries relating to Canada’s involvement in Somalia and the transcripts of the Canadian Blood Committee, have been used as evidence to support the opinion that there is a blatant disregard for the public record. In light of these incidents, questions have been raised concerning the alteration of records and the practice of not recording decisions or deliberations. What has been the impact of the ATIA on record-keeping in the Government of Canada? To what extent have records not been created as a result of the passing of the ATIA in 1983? This paper ventures into unknown territory by examining a range of records created by a number of departments both before and after the promulgation of the Act, with the intention of shedding light on the impact of ATIA on record-keeping in the federal government. RÉSUMÉ Le débat autour de la Loi sur l’accès à l’information (LAI) a surtout porté sur le manque de volonté du gouvernement de respecter la loi et son esprit. Alors que les rapports du Commissaire à l’information ont mis en relief des infractions comme des délais dans les réponses aux demandes ou encore une application trop large des exceptions accordées par la loi, d’autres ont allégué qu’une telle loi avait renforcé la résistance du gouvernement à être scruté par le biais de ses documents. Plus encore, les révélations des médias sur les enquêtes concernant la destruction possible de documents, tels que les journaux de guerre relatifs à l’implication du Canada en Somalie ou les transcriptions du Comité canadien du sang, ont été présentées comme illustration d’un grand mépris pour les documents gouvernementaux. À la lumière de ces incidents, on a soulevé des questions concernant l’altération des documents et la pratique d’éviter de documenter les décisions et les délibérations. Quel fut vraiment l’impact de la LAI sur la gestion des documents du gouvernement du Canada? Jusqu’à quel point at-on omis de créer des documents à la suite de l’adoption de la loi en 1983? Cet article se lance en territoire inconnu en examinant une série de documents créés par quelques ministères tant avant qu’après la promulgation de la loi avec l’intention de lever le voile sur l’impact de la LAI sur la gestion des documents au sein du gouvernement fédéral.